Impact of Gender on 30-Day Complications After Adult Spinal Deformity Surgery. Issue 14 (15th July 2016) - Kothari, Parth; Lee, Nathan J.; Leven, Dante M.; Lakomkin, Nikita; Shin, John I.; Skovrlj, Branko; Steinberger, Jeremy; Guzman, Javier Z.; Cho, Samuel K.
Abstract : Study Design: Retrospective study of prospectively collected data. Objective: To determine if postoperative morbidity for patients undergoing spinal deformity surgery varies by sex. Summary of Background Data: Influence of sex has been investigated in other surgical procedures but has not yet been studied in adult spinal deformity surgery. Methods: The American College of Surgeons National Surgical Quality Improvement Program is a large multicenter clinical registry that prospectively collects preoperative risk factors, intraoperative variables, and 30-day postoperative morbidity and mortality outcomes from about 400 hospitals nationwide. Current Procedural Terminology codes were used to query the database for adults who underwent fusion for spinal deformity. Patients were separated into groups of male and female sex. Univariate analysis and multivariate logistic regression were used to analyze the effect of sex on the incidence of postoperative morbidity and mortality. Results: Female sex was found to be a predictor of any complication[odds ratio (OR): 1.4, 95% confidence interval (CI) 1.2–1.7, P  < 0.0001], intra- or postoperative RBC transfusion (OR: 1.6, 95% CI 1.4–1.9, P  < .0001), urinary tract infection (OR: 2.0, 95% CI 1.2–3.3, P  = 0.0046), and length of stay >5 days (OR: 1.3, 95% CI 1.1–1.5, P  = 0.0015). Male sex was associated with higher rate of pulmonary (2.9% vs . 2.0%, P  = 0.0344) and cardiac complications (0.9% vs . 0.5%, P  = 0.0497). However, male sex as an independent risk factor for pulmonary (OR: 1.4, 95% CI 1.0–2.1, P  = 0.0715) and cardiac complications (OR: 1.9, 95% CI 0.9–4.0, P  = 0.1076) did not reach significance. Conclusion: Female sex was found to increase overall morbidity, particularly for urinary tract infection, transfusion, and length of stay >5 days. Male sex was associated with greater incidence of pulmonary and cardiac complications. Thus, sex and other patient characteristics highlighted must be considered as part of surgical risk planning and patient counseling. Level of Evidence: 3